FACTORS AFFECTING COMMUNITY INTEREST IN THE USE OF NON-CASH (DIGITAL) PAYMENTS - Sari, Vivi Nila; Anggraini, Dian (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This study aims to analyze and provide empirical evidence regarding the effect of perceived usefulness and perceived ease of use of non-cash (digital) payments with the use attitude as an intervening variable. The population in this study was the Islamic Community of West Sumatra. The sampling method used in this research was a number of 100 West Sumatran people using quota sampling. Data processing with SmartPLS 3.0 shows the results show perceived benefit has a positive effect on non-cash payments (digital). The higher the perception of benefit, the higher the non-cash payment (digital). Perception of Ease has a positive effect on Non-Cash (Digital) Payments. The higher the perception of ease, the higher the non-cash payment (digital).And Perceptions of Benefit have a positive effect on User Attitudes. The higher the perceived usefulness, the higher the user's attitude. Then the Ease of Perception has a positive effect on User Attitudes. The higher the perception of Ease, the higher the User's Attitude. User Attitudes have a positive effect on Non-Cash (Digital) Payments. The higher the User Attitude, the higher the use of Digital Payments. The indirect effect is greater than the direct effect, so it can be said that the User Attitude variable is perceived as an intervening variable between the Perception of Benefit and Perception of Ease with the Non-Cash Payment (Digital) variable.